The haunted mansion - Gunn, Andrew, 1969-; Hahn, Don.; Berenbaum, David; Minkoff, Rob.; Murphy, Eddie, 1961-; Stamp, Terence; Parker, Nathaniel, 1962-; Thomason, Marsha, 1976-; Tilly, Jennifer, 1958-; Shawn, Wallace; Walt Disney Pictures; Gunn Films (Firm); et al. ([United States] : Walt Disney Home Entertainment ; Burbank, CA : Distributed by Buena Vista Home Entertainment, 2004)
Jim Evers is a real estate agent whose latest project is to find a buyer for a huge but dilapidated old house in New Orleans. However, when Evers and his family visits the property before their family vacation, he discovers it's already inhabited by 999 ghosts, none of whom are interested in sharing the space. As the spirits make their displeasure known, Evers and his family, with the help of an eccentric medium named Madame Leota, try to get the ghosts to leave.
Originally released as a motion picture in 2003.
Special features: deleted scenes; bloopers; 'Haunted mansion' attration virtual tour - exploring the mansion with ghost guides Emma & Ezra; Raven "Superstition" music video; "The making-of" 'The mansion' - behind-the-scenes look at making 'The haunted mansion'; anatomy of a scene - ghost in the graveyard; audio commentaries; DVD-ROM content: the history of 'The haunted mansion' attraction; morphing ghost host maker; photo gallery; desktop themes/ wallpaper/screensavers; enhanced virtual mansion tour.
Director of photography, Remi Adefarasin ; editor, Pricilla Nedd-Friendly ; music, Mark Mancina ; costume designer, Mona May ; production designer, John Myhre ; visual effects supervisor, Jay Redd.
Eddie Murphy, Terence Stamp, Nathaniel Parker, Marsha Thomason, Jennifer Tilly, Wallace Shawn, Dina Waters, Marc John Jefferies, Aree Davis.
MPAA rating: PG; for frightening images, thematic elements and language.
DVD.
Keywords: Haunted houses -- Drama; Ghosts -- Drama; Real estate agents -- Drama; Feature films; Films for the hearing impaired